Stugotz's personal record book : the real winners and losers in sports - Weiner, Jon; Stanczyk, Dan (Random House, 2024)
"The 2020 MLB season didn't happen. Bill Belichick is not the greatest NFL coach of all time. Rafael Nadal is not on the Mount Rushmore of men's tennis. For years, popular sports radio personality Stugotz has been telling fans that he keeps a "personal record book," a kind of alternate sports universe in which Villanova did not beat Georgetown in the 1985 Men's National Championship game and Joe Namath is not in the Pro Football Hall of Fame. And while his arguments might seem like broadsides meant to rattle the cages of avid sports fans, they actually contain a lot more truth than one might think. Stugotz lays out his judgements with conviction and hilarity. His arguments may be controversial, but they're undeniably thought-provoking and hugely entertaining as he expertly dissects decisions and plays to highlight where integrity and sportsmanship have faded away. He takes rings away, gives them out, and declares entire sports dead. He even invites some of the biggest names in sports to offer their rebuttals. By taking on basketball, baseball, hockey, soccer, and even horse racing, Stugotz leaves no stone unturned and no sport unscathed"--